2020
DOI: 10.1016/j.sjbs.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing nutrient salts and trace metals distributions in the coastal water of Jeddah, Red Sea

Abstract: In this study, eighteen sites at Jeddah coastal area, Red Sea, have been assessed for water quality status, depending on nutrients, metals, Chlorophyll-a (Chl-a) and physical variables during 2018 and 2019. The investigated parameters of the Water Quality Index (WQI) are temperature, pH, salinity, dissolved oxygen (DO), DO saturation, oxidizable organic matter (OOM), suspended particulate matter (SPM), Chl-a, ammonium, nitrite, nitrate, total nitrogen, reactive phosphate, total phosphorus, silicate, Zn, Fe, Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…In this study, the values of Zn content were in the range from 2.77 at St.VI to 4.42 μg L −1 at St. III with an average 3.54 ± 0.60 μgL −1 .Cu concentration ranging between 0.81 at St. II and 1.54 μgL −1 at St.VI with an average 1.20 ± 0.26 μg L −1 . These values of zinc and copper in the present study were less compared with those reported by Al-Mur (2020) [28]; it was in the range from 22.0 ± 8.0 to 19.50 ± 6.80 μgL −1 for Zn, and 1.67 ± 0.60 and 3.20 ± 1.10 μgL −1 for Cu. The previous studies showed a strong relationship between each biological factor and the accumulation of trace metals in plants and microorganisms.…”
Section: Dissolved Metal Concentrationcontrasting
confidence: 96%
See 2 more Smart Citations
“…In this study, the values of Zn content were in the range from 2.77 at St.VI to 4.42 μg L −1 at St. III with an average 3.54 ± 0.60 μgL −1 .Cu concentration ranging between 0.81 at St. II and 1.54 μgL −1 at St.VI with an average 1.20 ± 0.26 μg L −1 . These values of zinc and copper in the present study were less compared with those reported by Al-Mur (2020) [28]; it was in the range from 22.0 ± 8.0 to 19.50 ± 6.80 μgL −1 for Zn, and 1.67 ± 0.60 and 3.20 ± 1.10 μgL −1 for Cu. The previous studies showed a strong relationship between each biological factor and the accumulation of trace metals in plants and microorganisms.…”
Section: Dissolved Metal Concentrationcontrasting
confidence: 96%
“…But, it can be interpreted by the oxidation process of ferrous to iron hydroxides. This result was observed from previous studies [28,74].…”
Section: Dissolved Metal Concentrationsupporting
confidence: 91%
See 1 more Smart Citation
“…Si-SiO 4 is strongly related to Total N (value = 0.88; p = 0.0078). This relationship seems to be owed to their importance for the algal growth and, hence, chl-a concentration [38].…”
Section: Correlationsmentioning
confidence: 97%
“…The distinct biodiversity of the Red Sea is a result of its high salinity range, and more than 1,000 species of invertebrates have been documented ( Al-Mur, 2020 ). However, it is crucial to exploring bioactive substances created by marine invertebrates.…”
Section: Introductionmentioning
confidence: 99%